Factors that contribute to workplace stress at HRM division in Petronas Carigali Sdn Bhd (PCSB) / Amirah Amir - Amir, Amirah (Faculty of Business and Management, 2014)
This study conducted to identify the factors that contribute to workplace stress. The researchers have chosen HRM Division in Petronas Carigali Sdn Bhd (PCSB) to represent this study. Researchers have listed three variables which are support at work, work overload and workplace bullying as the independent variables and workplace stress as the dependent variable. The researcher distributed 70 set of questionnaires to respondents which are employees at HRM division in PCSB. This study discussed the factors that improve and reduce workplace stress in PCSB and those factors will be the outcome of this study. The finding and analysis were made based on Statistical Package for Social Science (SPSS) version 20.0 to analyze the data. The finding of this study proves that the support at work, work overload and workplace bullying influenced the level of stress in the workplace. Support at work appears to be the most influenced factor towards workplace stress at HRM Division in Petronas Carigali Sdn Bhd.